STRATEGIC COMPENSATION DESIGN AND MARKETING SUCCESS: AN EMPIRICAL STUDY OF FACILITATIVE EMPLOYEE ALLOWANCES - Indra Lukmana Putra; Candrawati Triesti; Peni Puspitasari; Yekie Senja Oktora (Center for Indonesian Accounting Studies, 2025)
Research Objective - examine impact facilitative allowances specifically beauty, clothing, and communication allowances marketing performance of employees. Focuses how allowances influence motivation, productivity, customer engagement, and achievement of sales targets, as well as their role in strengthening professional image and client trust. Research Method – quantitative research employed using a survey method. Data collected h questionnaires distributed to marketing staff service and retail sectors in Indonesia, purposive sampling techniques. Multiple linear regression analysis SPSS to measure both the simultaneous and partial effects of the allowances on marketing performance. Research Findings – reveal beauty, clothing, and communication allowances simultaneously get positive and significant effect on marketing performance. Communication allowance strongest influence, followed clothing allowance and beauty allowance. Marketing employees who receive facilitative benefits tend more motivated, productive, and effective in building customer relationships, turn boosts sales performance. Theoretical and Policy Implications – marketing and human resource management theories highlighting employee appearance and communication skills suddenly key drivers customer trust and brand image. For management, allocating allowances support marketing employees appearance and communication effectiveness can serve strategic investment competitiveness and market reach. Novelty of the Research – combined effect non-financial facilitative allowances on marketing performance rarely addressed previous research. Allowances are not merely aesthetic or operational perks, but strategic tools, enhance sales outcomes and strengthen brand positioning.